Implementasi Peraturan Pemerintah Republik Indonesia Nomor 50 Tahun 2012 Tentang Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja (Studi Kasus PT. PLN Yogyakarta) - Bintang Damario Primayudha; Mustika Prabaningrum Kusumawati (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research has a background on the implementation of SMK3 at PT. PLN Yogyakarta, aims to answer questions based on the formulation of the problem, firstly How is the implementation of Government Regulation of the Republic of Indonesia Number 50 of 2012 concerning the Implementation of the Occupational Safety and Health Management System at PT PLN Yogyakarta, and secondly What are the inhibiting factors in the implementation of Government Regulation of the Republic of Indonesia Number 50 of 2012 concerning the Implementation of the Occupational Safety and Health Management System at PT PLN Yogyakarta. The type of research conducted by the author uses a combination of empirical and normative legal research, this research also uses a statutory and conceptual approach. The legal materials used are primary and secondary legal materials, and are analyzed using qualitative methods. The results of this study answered related to the formulation of the problem which showed that, first, PT. PLN Yogyakarta has guaranteed the Occupational Safety and Health of workers or laborers in accordance with the mandate in Article 1 point 2 of Government Regulation Number 50 of 2012 concerning the Implementation of the Occupational Safety and Health Management System, the second majority occurs due to Human error or negligence caused by the field workers itself and that the process of monitoring and evaluating SMK3 at PT. PLN Yogyakarta is appropriate because when the author conducted an interview with Mr. Catur Rizkyanto as the K3L and Security Team Leader.